Chirostylidae of Australia’s western continental margin (Crustacea : Decapoda : Anomura), with the description of five new species - Mccallum, Anna W.; Poore, Gary C. B. (Zootaxa, 2013)
Five new species from the squat lobster family Chirostylidae are described from the continental margin of western Aus-tralia: Uroptychus albus sp. nov., Uroptychus bardi sp. nov., Uroptychus jawi sp. nov., Uroptychus taylorae sp. nov., and Uroptychus worrorra sp. nov. New records of Indo-West Pacific species for Australia are: Gastroptychus brachyterus Ba-ba, 2005, Gastroptychus investigatoris Alcock, 1899, Uroptychodes grandirostris (Yokoya, 1933), Uroptychodes mortenseni (Van Dam, 1939), Uroptychus scandens Benedict, 1902, Uroptychus ciliatus (Van Dam, 1933) and Uroptychus vandamae Baba, 1988. New distributional records are given for species previously recorded from Australia: Uroptychus flindersi Ahyong & Poore, 2004, Uroptychus hesperius Ahyong & Poore, 2004, Uroptychus joloensis Van Dam, 1939, Uroptychus nigricapillis Alcock, 1901, and Uroptychus spinirostris (Ahyong & Poore, 2004). These new records expand the number of chirostylid species in Australia from 34 to 46. Keys to Australian species of the genera Gastroptychus, Uroptychodes and Uroptychus are provided.